Effect of DNA on the conformational dynamics of the endonucleases I‐DmoI as provided by molecular dynamics simulations. Issue 12 (22nd September 2016) - Grottesi, Alessandro; Cecconi, Simone; Molina, Rafael; D'abramo, Marco
Abstract: The conformational behavior of the wild‐type endonucleases I‐DmoI and two of its mutants has been studied in the presence and in the absence of DNA target sequences by means of extended molecular dynamics simulations. Our results show that in the absence of DNA, the three protein forms explore a similar essential conformational space, whereas when bound to the same DNA target sequence of 25 base pairs, they diversify and restrain the subspace explored. In addition, the differences in the essential subspaces explored by the residues near the catalytic site for both the bound and unbound forms are discussed in background of the experimental protein activity.